The Sustainability Business of Indonesian Commercial Banks as Measured by Regulatory Compliance - Puspitasari, Elen; Sudiyatno, Bambang; Masdjojo, Gregorius N; Andraini, Fitika; Nurhayat , Ida; Darodjat , Tubagus Achmad (Journal Evidence Of Law, 2024)
This research aimed to examine the relationship between the sustainability of bank business measured by bank performance and compliance with banking regulations. Bank compliance related to capital requirements, liquidity, and asset quality. This research uses quantitative methods to analyze the effect of compliance with banking regulations on bank performance. The research sample is a conventional private bank operating on the Indonesian Stock Exchange. The research period 2017 – 2021(before and during COVID-19) with 25 banks that met the requirements was taken as the research sample. Data analysis uses Panel Estimation Corrected Standard Errors. The outcome demonstrates that strengthening bank performance is positively impacted by capital requirements compliance, especially return on assets, but has no effect on return on equity. Compliance with liquidity and asset quality does not affect bank performance. Another finding is that inflation functions as a control variable for bank performance, while bank size does not. Ultimately, these findings show that a bank must comply with capital adequacy requirements because it has been proven to improve its sustainability business.